1992
DOI: 10.1111/j.1751-1097.1992.tb02236.x
|View full text |Cite
|
Sign up to set email alerts
|

Events in the Phytochrome Molecule After Irradiation

Abstract: Abstract-The photoconversion of Pr to Pfr has been investigated by a large number of investigators. We have previously demonstrated that Z,E isomerization of the tetrapyrrole chromophore is involved in the photoconversion. It is the best candidate for the primary photoreaction. Conformation and configuration of the Pr chromophore will be compared with that of chromophores in phycocyanin. The crystal structure of phycocyanin had been elucidated by x-ray analysis. Proton transfer and/or Z, E isomerization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 70 publications
0
22
0
Order By: Relevance
“…2). This result clearly suggests that a red light and a far-red light-absorbing intermediate are reversibly interconverted upon irradiation as it is the case in the plant photoreceptor phytochrome [8,9].…”
Section: Resultsmentioning
confidence: 71%
“…2). This result clearly suggests that a red light and a far-red light-absorbing intermediate are reversibly interconverted upon irradiation as it is the case in the plant photoreceptor phytochrome [8,9].…”
Section: Resultsmentioning
confidence: 71%
“…The resulting Pfr chromophore is more exposed to the medium than the Pr chromophore (Furuya & Song, 1994;Hahn et al, 1984;Chai et al, 1987;Singh et al, 1989;Vierstra & Quail, 1983). Studies have shown that in Pfr the distance between the N-terminus and the chromophore decreases by 12 Å Parker et al, 1992), and the protein responds with an increase in the N-terminus helicity (Singh et al, 1989;Rüdiger, 1992). The importance of this increase in helicity for the regulation of photomorphogenic processes by Pfr is underscored by the observation that the N-terminus is required for full physiological activity (Cherry et al, 1992;Stockhaus et al, 1992).…”
mentioning
confidence: 96%
“…The photochemical interconversion processes of phytochromes have been extensively studied for many years (Butler 1972;Kendrick and Spruit 1977;Rüdiger 1992;Braslavsky et al 1997;Braslavsky 2003). Since Pr and Pfr have overlapping absorption spectra in most regions of the light spectrum, Pr-to-Pfr and Pfr-to-Pr photoconversion processes lead to the formation of a photoequilibium consisting of a mixture of Pr and Pfr forms under saturating illumination.…”
Section: Phytochrome Photointerconversionsmentioning
confidence: 99%